1983
DOI: 10.1055/s-0038-1657336
|View full text |Cite
|
Sign up to set email alerts
|

Platelets, Coagulation and Fibrinolysis in Patients with Diabetic Retinopathy

Abstract: SummaryTwenty control subjects, 12 insulin treated and 10 non-insulin treated diabetics were studied. All diabetics had retinopathy documented by fluorescein angiography and fluorophotometry. Factor VUIRiAg and plasma fibrinogen concentrations were elevated in both diabetic groups, but more so in the insulin treated patients. Within this latter group the plasma fibrinogen was also correlated with the degree of retinopathy.Platelets separated on linear isosmolar Percoll gradients showed an increase in intraplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Fritschi et al (1984) found some degree of hyperreactivity in diabetics only in the case of vascular complicationa (macroangiopathy), without those there was a normal aggregation behaviour. On the, other hand, Greco et al (1985) reported a greater sensitivity of diabetic platelets after challenge with PAF Using ADP as an agonist we found some degree of hyperreactivity, which is consistent with the majority of studies published in the literature (Banga and Sixma, 1986;Ostermann and Van de Loo, 1986;Winocour et al, 1985), but also here a number of reports appeared showing no difference in aggregation between diabetics and healthy donors (Brooks et al, 1983;Corbella et al, 1979;Peterson and Gormsen, 1978;Porta et al, 1982;Rao et al, 1984). Therefore, it is difficult to establish whether or not platelet aggregation is increased or normal in diabetics, since studies reported in the literature suggest both possibilities.…”
Section: Discussionsupporting
confidence: 91%
“…Fritschi et al (1984) found some degree of hyperreactivity in diabetics only in the case of vascular complicationa (macroangiopathy), without those there was a normal aggregation behaviour. On the, other hand, Greco et al (1985) reported a greater sensitivity of diabetic platelets after challenge with PAF Using ADP as an agonist we found some degree of hyperreactivity, which is consistent with the majority of studies published in the literature (Banga and Sixma, 1986;Ostermann and Van de Loo, 1986;Winocour et al, 1985), but also here a number of reports appeared showing no difference in aggregation between diabetics and healthy donors (Brooks et al, 1983;Corbella et al, 1979;Peterson and Gormsen, 1978;Porta et al, 1982;Rao et al, 1984). Therefore, it is difficult to establish whether or not platelet aggregation is increased or normal in diabetics, since studies reported in the literature suggest both possibilities.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported an association between fibrinogen level and diabetic retinopathy[10–16]. It has, however, yet to be determined whether the reported association is independent , because in most of the studies[10–13, 16], confounding factors such as blood pressure and lipid levels, which are correlated with plasma fibrinogen level[7, 9, 17, 18], and are simultaneously known as potential risk factors for diabetic retinopathy[2, 16, 19–23], were not controlled. To address whether the association between fibrinogen level and diabetic retinopathy is independent or just a secondary effect of other confounding factors, we performed multiple logistic regression analyses and the results supported an independent association.…”
Section: Discussionmentioning
confidence: 99%
“…High plasma fibrinogen level is an accepted risk factor for cardiovascular disease in patients with DM[6–8] and in the general population[9]. There have been several studies reporting an association between plasma fibrinogen level and diabetic retinopathy[10–16]. Most, however, did not control for other confounding variables, such as lipid profile and blood pressure, which correlate with plasma fibrinogen level[7, 9, 17, 18] and are also recognized risk factors for diabetic retinopathy[2, 16, 19–23].…”
Section: Introductionmentioning
confidence: 99%
“…Basement membrane thickening, microaneurysms and capillary occlusions have been reported and would serve as pathological substrate for the diabetic microangiopathy. 57,71,72…”
Section: Introductionmentioning
confidence: 99%